Letter from Carl D. Duncan to Patricia Whiting, August 16, 1966 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan compliments Whiting on her inspiring personality and considers taking night classes for fun.